2017
DOI: 10.1111/crj.12662
|View full text |Cite
|
Sign up to set email alerts
|

Chronic coffee consumption and respiratory disease: A systematic review

Abstract: Coffee consumption was associated with some positive effects on the respiratory system. There was however limited available evidence, mostly from cross sectional and retrospective studies. The only prospective cohort studies were those reporting on respiratory mortality. These results suggest that coffee consumption may be a part of a healthy lifestyle leading to reduced respiratory morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
0
18
1
1
Order By: Relevance
“…Whereas smoking and alcohol are deleterious agents for cardiovascular system and lung integrity that may facilitate or aggravate pulmonary infectious diseases, the explanation for the benefit of coffee or tea consumption is unclear. Coffee consumption is associated with some positive effects on the respiratory system [37], but perhaps in this cohort is also a surrogate of social habits with impact on the risk of viral transmission. Mild cognitive impairment and dementia, mainly due to neurodegenerative disease, were also found to be associated with the severity of COVID-19 in accordance with previous reports [15].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas smoking and alcohol are deleterious agents for cardiovascular system and lung integrity that may facilitate or aggravate pulmonary infectious diseases, the explanation for the benefit of coffee or tea consumption is unclear. Coffee consumption is associated with some positive effects on the respiratory system [37], but perhaps in this cohort is also a surrogate of social habits with impact on the risk of viral transmission. Mild cognitive impairment and dementia, mainly due to neurodegenerative disease, were also found to be associated with the severity of COVID-19 in accordance with previous reports [15].…”
Section: Discussionmentioning
confidence: 99%
“…Given its widespread consumption, interest has been growing around the potential role of coffee in respiratory health. Findings from literature reviews point to an association between regular (not decaffeinated) coffee intake and improved lung function and reduced mortality from respiratory disease, but not COPD [107], with contributory roles for its constituents, caffeine (bronchodilator, anti-inflammatory) and polyphenols (antioxidant, anti-inflammatory). Smoking is a major confounder in these studies because it may accelerate the hepatic metabolism and clearance of caffeine or may dilute or dampen the beneficial effects of coffee through its potent pro-oxidant and pro-inflammatory action [107].…”
Section: Individual Foods and Nutrients Lung Function And Copdmentioning
confidence: 99%
“…A recent systematic review showed inconsistent results from three studies assessing the association between coffee consumption and asthma [ 8 ]. In a study using the Italian National Health Survey, the relative risks of bronchial asthma were 0.79 (95% CI = 0.69–0.91) for those who consumed two cups per day and 0.78 (95% CI = 0.69–0.88) for those who consumed three or more cups per day compared with subjects who did not drink coffee [ 9 ].…”
Section: Introductionmentioning
confidence: 99%